Pengaruh Asosiasi Warna dengan Makna Negatif pada Rasisme dalam Anak - Kristi Tamara Novitasari; Y. Bagus Wismanto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
Children shouldn’t hold biases or prejudices against any group, especially since their social world is still quite limited. However, studies show that color bias can start very early on, as children begin to associate certain colors with negative traits or meanings. This paper was conducted using descriptive literature review method and looked into how these early color associations might teach kids about racism. Previous studies have shown that children are capable of categorizing individuals based on their skin color and assigning specific meanings to certain skin tones, which may lead to the development of bias within the child and ultimately result in the practice of colorism and racism. By reviewing existing research on how children perceive colors, this paper explains how color bias emerges and subsequently develops into colorism. The researchers connected theories of racism, colorism, and children's learning processes with how children absorb information from the surrounding environment, use imitation and influenced by other people. This paper also highlights the importance of the role of parents and educators in breaking the cycle of colorism for future generations by providing education and initiating discussions about colorism before the concept becomes ingrained in children.